Perancangan Dashboard Performa Kapal pada Sistem E-Filing International Safety Management Code: Studi Kasus - Aileen Tusita Devi; Siana Halim; Karina Agustin (Jurnal Titra, 2021)
The purpose of this research is to design a ship performance dashboard for the e-filing International Safety Management (ISM) Code system at a company in Surabaya. E-filing system is a system for filling and sending reports by ship crew at sea to the office. The purpose of the e-filing system is to simplify monitoring ISM Code implementation from the office. But in practice, some problems occurred in the system. Office crews need a long time to process the data and there is not enough information to make a decision. However, the problem can be solved by designing a ship performance dashboard. The dashboard objective is to visualize the important data from the ship so that the company can access the needed information. The dashboard design is based on reports that are sent by the ship crew and then processed with software. Processing data with software can make it easier and faster for the company. The processed data will be visualized using a dashboard for different purposes based on the information that’s needed. Overall, dashboard visualization will provide information about ship audit progress, machine damage and repairment that occurred, main engine indicator, and warning system for each main engine and generator component running hours.